Sites of learning: Exploring political ecologies and visceral pedagogies of surplus food redistribution in the UK. Issue 7 (October 2019) - Spring, Charlotte; Adams, Mags; Hardman, Michael
Drawing on ethnographic research with organisations redistributing wasted food, this paper explores potentials for political and ethical learning by comparing different approaches to food handling and teaching. Food acts as instigator and tool for learning about ecological impacts, wellbeing, provenance, health and pleasure. Re-learning wasted food challenges accusations of its stigmatising potential while attempting to address serious material issues of food insecurity and food access. Taking seriously the charge that 'community-level' approaches might depoliticise and individualise food distribution at the expense of structural critique and action, these pragmatic and polysemic enrolments of food waste can nevertheless embody a teleology of change, through changing practices of food handling and fostering critical understandings of food system issues. While acknowledging the spatial, temporal and technological mediators of food's journey from bin towards mouth, attention is paid to the sensorial, embodied and affective means by which the food/waste distinction is known and taught/learned. A political ecology of the body framework is used to explore the 'visceral realm' of food access as always part-situated in learners' diverse foodscapes. These visceral pedagogies of knowing food sit alongside the power dynamics of regulatory food governance in the form of, for example, expiry date labels. In short, these practices, albeit rooted in environmentally damaging and unequally distributed foodscapes requiring systemic transformation, can nevertheless foster more vibrant sympathies between people and food, more careful connections between learners and their food futures.